10(c-7)=-36

Simple and best practice solution for 10(c-7)=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(c-7)=-36 equation:


Simplifying
10(c + -7) = -36

Reorder the terms:
10(-7 + c) = -36
(-7 * 10 + c * 10) = -36
(-70 + 10c) = -36

Solving
-70 + 10c = -36

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '70' to each side of the equation.
-70 + 70 + 10c = -36 + 70

Combine like terms: -70 + 70 = 0
0 + 10c = -36 + 70
10c = -36 + 70

Combine like terms: -36 + 70 = 34
10c = 34

Divide each side by '10'.
c = 3.4

Simplifying
c = 3.4

See similar equations:

| 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 |

Equations solver categories